2014
DOI: 10.1590/0102-311x00004613
|View full text |Cite
|
Sign up to set email alerts
|

Sobrepeso e obesidade abdominal em adultos quilombolas, Bahia, Brasil

Abstract: This study analyzes nutritional status, estimates the prevalence of overweight and abdominal obesity, and investigates factors associated with these outcomes in a two-stage random sample of adults (> 20 years) in quilombos (communities that descend from African slaves) in Vitória da Conquista, Bahia State, Brazil, in 2011. Among 739 participants, prevalence rates were 31.8% and 10.2% for overweight and obesity, respectively, and 55.7% for increased waist-to-height ratio (> 0.50). Prevalence of overweight was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
4
17

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 43 publications
4
19
4
17
Order By: Relevance
“…As situações de vulnerabilidade social nessas populações podem ser historicamente explicadas tanto pelo perío-do de escravidão no Brasil no século XIX, quanto pelas baixas condições socioeconômicas 11 e elevadas prevalências de DCNT 12,13 .…”
unclassified
“…As situações de vulnerabilidade social nessas populações podem ser historicamente explicadas tanto pelo perío-do de escravidão no Brasil no século XIX, quanto pelas baixas condições socioeconômicas 11 e elevadas prevalências de DCNT 12,13 .…”
unclassified
“…(7) In this context, the marriage or stable union can positively affect the health, but can also affect it negatively After establishment of a stable relationship, weight gain can be observed, which increases the proportions of men and women with excessive weight. (11) The marital status, "with partner", identified in this study showed a statistically significant association with excessive weight in both bivariate (OR=1.79;[1.19;2.68];p= 0.005) as well as in the multivariate analysis (OR=1.54;[1.01;2.37];p=0.047). Corroborating these findings, a survey conducted in the metropolitan area of Fortaleza, Ceará, Brazil (7) identified factors for overweight in young adults.…”
Section: Discussionmentioning
confidence: 60%
“…Observa-se que o estado nutricional da comunidade quilombola acompanha as tendências atuais, com aumento do sobrepeso e obesidade na população (20) . Em estudo com adultos residentes em comunidades quilombolas na cidade de Vitória da Conquista, Bahia, ao descrever o perfil antropométrico da população, observou-se também altas prevalências de sobrepeso e obesidade, de 31,8% e 10,2%, respectivamente (21) . Considera-se uma situação de risco à saúde quilombola uma vez que o sobrepeso é um fator contribuinte no aumento das taxas de morbidade e mortalidade.…”
Section: Resultsunclassified